Dobór szczepów drożdży paszowych do zdrożdżowania rolniczych wywarów gorzelniczych - Pieciuń, Tomasz; Leśniak, Władysław (Selection of Fodder Yeast Strains to Cultivate Biomass on Agricultural Starch Stillage, 2008)
The main problem for distillery owners is disposal of unusable waste, which remains after ethanol evaporation from post fermentation broth, so-called agricultural starch stillage. Due to the dominant tendency among enterprises to minimize costs of production by appropriate waste management, there appeared the need of working out an optimal method of waste utilization. According to existing experimental results and to distillery practices several methods of waste utilization were created, however they generate high costs and the application of them is unprofitable. Currently the only way of agricultural starch stillage is its cultivation. This paper presents the preliminary study to increase the content of protein in starch stillage during fodder yeast cultivation process. Experiments concerned the selection of fodder yeast culture and optimization of cultivation medium with addition of diammonium phosphate and potassium phosphate to agricultural starch stillage and resulted in obtaining a protein containing by-product, which can be used as fodder for animals. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 143-151